Life-threatening hyponatraemia - Egom, Emmanuel Eroume A (BMJ Publishing Group, 2011)
A 31-year-old hypertensive woman was admitted to hospital with palpitations. Her hypertension was treated with bendroflumethiazide, which had been increased from 2.5 to 5 mg daily by her general practitioner about 18 months prior to her admission. She was also on ramipril 10 mg once daily. There were no abnormal findings on examination, and a 12-lead ECG showed sinus rhythm, rate 75, with Q waves in leads V1–V2. Telemetry (over 24 h) showed ventricular bigeminy when she had her typical palpitations. Her admission serum sodium and potassium concentrations were 132 and 3.4 mmol/l, respectively. Immediately prior to planned discharge the following day, she experienced paraesthesiae, weakness, confusion and seizures accompanied by 10 s asystole on the ECG monitor. Her serum sodium had fallen to 120 mmol/l and potassium to 2.3 mmol/l. Bendroflumethiazide and ramipril were discontinued and the patient was restricted to fluids of 1.5 l/24 h. She also received potassium supplements. Her serum sodium concentration rose to normal over 6 days, and she was discharged on feeling well.